ESTIMASI HARGA SEWA ALATBERAT MENGGUNAKAN LINEAR REGRESSION PADA PT FANBEL JAYA BERSAMA - Deason Tanduri; Tri Agus Setiawan (Politeknik Bisnis Indonesia, 2023)
PT Fanbel Jaya Bersama is a company engaged in the construction sector, especially heavy equipment rental. The rental price of PT Fanbel Jaya Bersama needs to be implemented to process heavy equipment rental data using a linear regression algorithm. This study uses a simple linear regression method to find the estimated price that is rented out to consumers. For deployment using a chatbot that displays estimates and data in the form of descriptions of suitable datasets displayed to consumers. In this study, 2 independent variables were used, namely the unit of minutes of rent (X) and the dependent variable, namely the rental price (Y). From the 9 processed data, the RMSE value is 3100946.073781. From this study the linear regression algorithm is accurate and precise. The results of this study display prices that have been predicted by chatbots for consumers who want to look for heavy equipment. Further development will be promoted through the website with the same simple linear regression method and more data from other universities.